2013
DOI: 10.48550/arxiv.1305.3464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Globally Generated Vector Bundles on P^n with c_1=4

Abstract: We provide a complete classification of globally generated vector bundles with first Chern class c 1 ≤ 5 one the projective plane and with c 1 ≤ 4 on the projective n-space for n ≥ 3. This reproves and extends, in a systematic manner, previous results obtained for c 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…and so E admits the following resolution (1). Similarly when deg(Z) = 2, we obtain the resolution (2).…”
Section: Rank Two Globally Generated Vector Bundle Withmentioning
confidence: 72%
See 3 more Smart Citations
“…and so E admits the following resolution (1). Similarly when deg(Z) = 2, we obtain the resolution (2).…”
Section: Rank Two Globally Generated Vector Bundle Withmentioning
confidence: 72%
“…E fits into the sequence (4) with c 1 = (1, 2). Since I Z (1, 2) is globally generated, Z is contained in a complete intersection of two hypersurfaces of bidegree (1,2) in Q. In particular, deg(Z) is at most 4.…”
Section: Rank Two Globally Generated Vector Bundle Withmentioning
confidence: 99%
See 2 more Smart Citations
“…The m-effective pair associated to E is in this case (4, 6). In the recent work [ACM13] it is shown that the only possibilities for such a pair are to be associated to either a quotient of O P 2 (1) 4 , or a quotient of O P 2 (1) ⊕ O P 2 (2) ⊕ Q. The first case corresponds to a stable Steiner bundle, while the second one is semistable.…”
Section: Preliminariesmentioning
confidence: 99%